Voxel‐based morphometry in creative writers: Grey matter increase in a prefronto‐thalamic‐cerebellar network. (15th June 2018) - Neumann, Nicola; Domin, Martin; Erhard, Katharina; Lotze, Martin
Abstract: Continuous practice modulates those features of brain anatomy specifically associated with requirements of the respective training task. This study aimed to highlight brain structural changes going along with long‐term experience in creative writing. To this end, we investigated the grey matter volume of 23 expert writers with voxel‐based morphometry and compared it to 28 matched nonexpert controls. Expert writers had higher grey matter volume in the right superior frontal and middle frontal gyri (BA 9, 10) as well as left middle frontal gyrus (BA 9, 10, 46), the bilateral medial dorsal nuclei of the thalamus and left posterior cerebellum. A regression analysis confirmed the association of enhanced grey matter volume in the right superior frontal gyrus (BA 10) with practice index of writing. In region‐of‐interest based regression analyses, we found associations of grey matter volume in the right Broca's analogue (BA 44) and right primary visual cortex (BA 17) with creativity ratings of the texts written during scanning, but not with a standardised verbal creativity test. Creative writing thus seems to be strongly connected to a prefronto‐thalamic‐cerebellar network that supports the continuous generation, organisation and revision of ideas that is necessary to write literary texts. Abstract : Expert writers with an average writing experience of 12 years showed increased grey matter volume (GM) in bilateral prefrontal (BA 9, 10, left 46), thalamic (not visible in the segmented brain), and cerebellar regions compared to nonexperts. A practice index was positively associated with GM of the right superior frontal gyrus (BA 10). Creative writing seems to be strongly connected to a prefronto‐thalamic‐cerebellar network that supports the continuous generation, organization and revision of ideas.